Evidence for Late Holocene earthquakes on the Utsalady Point Fault, northern puget lowland, Washington - Johnson, S. Y.; Nelson, A. R.; Personius, S. F.; Wells, R. E.; Kelsey, H. N.; Sherrod, B. L.; Okumura, K.; Koehler, R.; Witter, R. C.; Bradley, L. A.; Harding, D. J. (Bulletin of the Seismological Society of America, 2004)
Trenches across the Utsalady Point fault in the northern Puget Lowland of Washington reveal evidence of at least one and probably two late Holocene earthquakes. The "Teeka"' and "Duffers" trenches were located along a 1.4-km-long. 1- to 4-m-high, northwest-trending, southwest-facing. topographic scarp recognized from Airborne Laser Swath Mapping. Glaciomarine drift exposed in the trenches reveals evidence of about 95 to 150 cm of vertical and 200 to 220 cm of left-lateral slip in the Teeka trench. Radiocarbon ages from a buried soil A horizon and overlying slope colluvium alone, with the historical record of earthquakes suggest that this faulting occurred 100 to 400 calendar years B.P. (A.D. 1550 to 1850). In the Duffers trench, 370 to 450 cm of vertical separation is accommodated by faulting (similar to210 cm) and folding (similar to160 to 240 cm), with probable but undetermined amounts of lateral slip. Stratigraphic relations and radiocarbon ages from buried soil, colluvium. and fissure fill in the hanging wall suggest the deformation at Duffers is most likely from two earthquakes that occurred between 100 to 500 and 1100 to 2200 calendar years B.P., but deformation during a single earthquake is also possible. For the two-earthquake hypothesis, deformation at Teeka trench in the first event involved folding but not faulting. Regional relations suggest that the earthquake(s) were M greater than or equal to similar to6.7 and that offshore rupture may have produced tsunamis. Based on this investigation and related recent studies, the maximum recurrence interval for large ground-rupturing crustal-fault earthquakes in the Puget Lowland is about 400 to 600 years or less.
887giTimes Cited:18Cited References Count:46